Assessment of Effective Dose of Levothyroxine in Treatment of Congenital Hypothyroid Babies: A Pilot Study (Bangladesh Journal of Nuclear Medicine, 2025)
Introduction: Congenital hypothyroidism (CH) is when newborns and infants have a low-functioning thyroid gland, leading to insufficient thyroid hormone production. Although affected babies may look normal at first, they can start to show symptoms within weeks or months after birth. The main treatment for congenital hypothyroidism is hormone replacement therapy, usually with levothyroxine (LT4). The American Academy of Pediatrics (AAP) and the European Society for Pediatrics Endocrinology (ESPE) recommend starting with a dose of 10 to 15 mcg/kg/day of levothyroxine. However, some studies suggest that using lower doses might still be effective while lowering the chance of an overdose on thyroxine. Objective: The aim of this study was to evaluate the optimal dose of levothyroxine in the treatment of congenital hypothyroidism in Bangladeshi infants. Materials and Methods: This study took place at the National Institute of Nuclear Medicine & Allied Sciences (NINMAS) from September 2022 to February 2024. A total of 29 newborns with diagnosed congenital hypothyroidism were enrolled. The infants received levothyroxine, prescribed mostly by physicians of Thyroid Division of NINMAS, though few of them were initially treated by outside physicians. Their thyroid hormone levels were regularly monitored with serum thyroid-stimulating hormone (TSH) test. The starting dose of levothyroxine and how long it took for the infants to reach a normal thyroid state were recorded. Results: Among 29 subjects, male to female ratio was 15:14. It was observed that 14% of the infants started with a dose of levothyroxine less than 6 mcg/kg/day, 31% received 6-7.9 mcg/kg/day, 27% got 8-9.9 mcg/kg/day, and 28% were given 10-14 mcg/kg/day. Infants who received lower initial doses (less than 10 mcg/kg/day) reached a normal thyroid state more quickly than those who started with higher doses (10-14 mcg/kg/day). Importantly, 21 out of the 29 infants received lower doses than the usual starting amount but still showed normal thyroid function without signs of overtreatment. Conclusion: Proper treatment of congenital hypothyroid babies is essential for appropriate growth and neurodevelopment. This study provided an important observation regarding effective dose of levothyroxine that will be helpful for adequate treatment planning of Bangladeshi congenital hypothyroid babies.Bangladesh J. Nuclear Med. 28(1): 98-104, 2025